Simplify 14 + 13 − (12 + 11). A) 0 B) 1 C) 4 D) 10

Question

Simplify 14 + 13 − (12 + 11). A) 0 B) 1 C) 4 D) 10

in progress 0
Kennedy 2 months 2021-10-05T15:48:30+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-05T15:50:14+00:00

    The answer is C) 4
    Explanation: Use order of operations (PEMDAS)
    Add what’s in the parenthesis (12+11) = 23
    Then add 14+13=27
    27 — 23 = 4

    0
    2021-10-05T15:50:16+00:00

    C. 4
    14 + 13 – (23)
    27 – 23
    4

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )